2019
DOI: 10.5194/acp-19-5771-2019
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of biomass burning pollution over tropical South America from aircraft in situ measurements during SAMBBA

Abstract: Abstract. We examine processes driving the vertical distribution of biomass burning pollution following an integrated analysis of over 200 pollutant and meteorological profiles measured in situ during the South AMerican Biomass Burning Analysis (SAMBBA) field experiment. This study will aid future work examining the impact of biomass burning on weather, climate and air quality. During the dry season there were significant contrasts in the composition and vertical distribution of haze between western and easter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 92 publications
(123 reference statements)
4
21
0
Order By: Relevance
“…The high EnRBC in African 685 plumes can be attributed to more flaming combustion in the comparatively dry grassland, savanna, and shrubland vegetation in contrast to more smoldering combustion of Amazonian deforestation fires in the moist tropical forests. For comparison, Darbyshire et al (2019) reported from the SAMBBA aircraft campaign over the southern Amazon basin, EnRBC of 3 ng m -3 ppb -1 in the west associated with more smoldering combustion of pasture and forested areas, in contrast to EnRBC of 12 ng m -3 ppb -1 in eastern part influ-690 enced by Cerrado fires. Note that differences between ground-based (this section) and aircraft EnRBC (section 3.1) presented in this paper are due to removal processes, combustion phase and, possibly, to the use of different measurement techniques.…”
Section: Estimated Relevance Of Pollution Layer For Central Amazonianmentioning
confidence: 94%
See 1 more Smart Citation
“…The high EnRBC in African 685 plumes can be attributed to more flaming combustion in the comparatively dry grassland, savanna, and shrubland vegetation in contrast to more smoldering combustion of Amazonian deforestation fires in the moist tropical forests. For comparison, Darbyshire et al (2019) reported from the SAMBBA aircraft campaign over the southern Amazon basin, EnRBC of 3 ng m -3 ppb -1 in the west associated with more smoldering combustion of pasture and forested areas, in contrast to EnRBC of 12 ng m -3 ppb -1 in eastern part influ-690 enced by Cerrado fires. Note that differences between ground-based (this section) and aircraft EnRBC (section 3.1) presented in this paper are due to removal processes, combustion phase and, possibly, to the use of different measurement techniques.…”
Section: Estimated Relevance Of Pollution Layer For Central Amazonianmentioning
confidence: 94%
“…The elevated cCO = 150 ± 30 ppb along with the high MrBC indicates that the UPL air masses originated from BB emissions. Moreover, the ratio between these two co-emitted species can be used as tracer for the origin and age of BB plumes (Darbyshire et al, 2019;Guyon et al, 2005;Saturno et al, 2018b). The aged UPL is characterized by a higher rBC enhancement ratio, EnRBC = 12.4 ± 0.2 ng m -3 ppb -1 compared to fresh Amazonian BB, with EnRBC of 7.8 ± 0.1 ng/m -3 ppb -1 (Fig.…”
Section: Offshore Aerosol Particle and Trace Gas Profilesmentioning
confidence: 99%
“…Monoterpenes are oxidised to form a product that condenses irreversibly in the particle phase (Scott et al, 2014). Size-resolved emissions of mineral dust are prescribed from daily varying emissions fluxes provided for AEROCOM (Dentener et al, 2006).…”
Section: Glomap Global Aerosol Modelmentioning
confidence: 99%
“…Marenco et al (2016) analysed lidar data during the SAMBBA campaign and found that the mean height of aerosol layers was 2.0 ± 0.4 km, suggesting that the majority of the aerosol is injected into the boundary layer. Fire emissions in GLOMAP are distributed vertically over six ecosystem-dependent altitudes between the surface and 6 km according to Dentener et al (2006). Over Brazil ∼ 53 % of emissions were injected below 500 m elevation, ∼ 30 % between 500 and 1000 m elevation, and ∼ 17 % between 1000 and 3000 m elevation.…”
Section: Biomass Burning Emissions In Glomapmentioning
confidence: 99%
“…Open circles represent extreme drought/anomalous fire years and are not included in trend analysis.10.1029/2019GL084143systematic positive bias of~5 ppbv (although this is within the observational variability). Comparisons with aircraft observations from the South AMerican Biomass Burning Analysis campaign(Darbyshire et al, 2019) (September-October 2012) show the model successfully reproduces the boundary layer vertical ozone profile between 30 and 45 ppbv, with a slight positive bias of 2-3 ppbv. These observations and comparison are also consistent with ozonesondes from Natal(2007)(2008).…”
mentioning
confidence: 84%